Banjir Jakarta 2007: Kegagalan Kolektif Pengelolaan Bumi - Pratiwi, Oktafiani Catur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
For many years flood has been annual problem in Jakarta. Apart from seeing flood as a natural dissaster brought by climate change and global zaarming effect, this paper argues that flood in Jakarta indicates a collective failure in urban development planning. Further this paper proposes a more comprehensive approach in anticipating the dissaster involving political, economical, technological, and ecological dimmensions.